Spatially Modulated Pumping for Cholesteric Liquid Crystal Lasers - Chanishvili, Andro; Chubinidze, Ketevan; Petriashvili, Gia; Ponjavidze, Nino; Wardosanidze, Zurab; Zurabishvili, Tsisana (Photonics Letters of Poland, 2025)
Excitation of cholesteric liquid crystal lasers with a large diameter pumping spot is considered. It is shown that the introduction of spatial modulation into the pump beam transfers light emission of the liquid crystal layer from the luminescence mode to the lasing mode. Furthermore, the possibility of dynamic recording of information on a laser optical layer with a thickness of 12µm and an area of about 40mm2 is demonstrated. Full Text: PDF References L. Blinov, R. Bartolino (Eds.), Liquid Crystal Microlasers (Trivandrum, Transworld Research Network 2010). DirectLink H. Coles, S. Morris, "Liquid-crystal lasers", Nature Photonics 10, 676 (2010). CrossRef A. Chanishvili, K. Chubinidze, G. Petriashvili, N. Ponjavidze, Z. Wardosanidze, Ts. Zurabishvili, "Enhanced cone-shaped lasing from cholesteric liquid crystals", Opt. Lett. 49(19), 5515 (2024). CrossRef O. Svelto, Principles of Lasers (Springer, New York 2010). CrossRef Z. Wardosanidze, A. Chanishvili, G. Petriashvili, G. Chilaya, "Cholesteric liquid crystal holographic laser", Opt. Lett. 39(4),1008 (2014). CrossRef